2020
DOI: 10.2217/pme-2019-0110
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Clinical Pharmacogenetics Studies in African Populations

Abstract: Effective interventions and treatments for complex diseases have been implemented globally, however, coverage in Africa has been comparatively lower due to lack of capacity, clinical applicability and knowledge on the genetic contribution to disease and treatment. Currently, there is a scarcity of genetic data on African populations, which have enormous genetic diversity. Pharmacogenomics studies have the potential to revolutionise treatment of diseases, therefore, African populations are likely to benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 123 publications
(153 reference statements)
0
27
0
Order By: Relevance
“…The African continent is the cradle of human origin and African populations are characterized by high genetic diversity and complex population structure. Despite this genetic variation, drug efficacy and safety have not been comprehensively studied in the populations of sub-Saharan Africa (SSA) (Radouani et al, 2020). This is of specific relevance to SSA, where high burdens of disease are amplified by non-optimal treatment outcomes.…”
Section: Rationalementioning
confidence: 99%
“…The African continent is the cradle of human origin and African populations are characterized by high genetic diversity and complex population structure. Despite this genetic variation, drug efficacy and safety have not been comprehensively studied in the populations of sub-Saharan Africa (SSA) (Radouani et al, 2020). This is of specific relevance to SSA, where high burdens of disease are amplified by non-optimal treatment outcomes.…”
Section: Rationalementioning
confidence: 99%
“…A number of African studies, were premised on observations from the USA and Europe, that showed association between warfarin drug response and variation in two genes, CYP2C9 and VKORC1. Associations between warfarin levels and VKORC1 and CYP2C9 genetic variants were corroborated in Egyptians, Ghanaians and South Africans, but not in Sudanese and Kenyan individuals [12]. Such results speak to the heterogeneity of Africans among themselves and with other populations.…”
mentioning
confidence: 84%
“…CYP3A4 and ABCB1 have been associated with response to cyclosporine therapy for renal transplant recipients; CYP3A4 and CYP3A5 haplotypes are associated with tacrolimus clearance, an immunosuppressive therapy sometimes used to treat SR-FSGS; and variants in CYP3A4 and ADRB2 have been associated with the blood pressure-lowering drugs amlodipine and ramipril, respectively. (83) The implementation of personalized pharmacogenetics in SSA requires additional genetic and clinical research, including clinical trials to identify population-specific variants that affect drug metabolism, clearance and clinical efficacy. An example is renal risk reduction (R3)-randomized clinical trial in Nigeria that is designed to study the efficacy of blocking the renin-angiotensin-aldosterone system with inexpensive ACEis to retard progression of kidney disease in patients with treated HIV infection and to determine if APOL1 HR status is associated with worse kidney outcomes among study participants.…”
Section: Genetic Testing For Personalized Medicine and Public Health In Africamentioning
confidence: 99%